The Relationship between Intelligence and Anxiety: An Association with Subcortical White Matter Metabolism - Coplan, Jeremy D.; Hodulik, Sarah G.; Mathew, Sanjay J.; Mao, Xiangling; Hof, Patrick R.; Gorman, Jack M.; Shungu, Dikoma C. (Frontiers in Evolutionary Neuroscience, 2012)
We have demonstrated in a previous study that a high degree of worry in patients with generalized anxiety disorder (GAD) correlates positively with intelligence and that a low degree of worry in healthy subjects correlates positively with intelligence. We have also shown that both worry and intelligence exhibit an inverse correlation with certain metabolites in the subcortical white matter. Here we reexamine the relationships among generalized anxiety, worry, intelligence, and subcortical white matter metabolism in an extended sample. Results from the original study were combined with results from a second study to create a sample comprised of 26 patients with GAD and 18 healthy volunteers. Subjects were evaluated using the Penn State Worry Questionnaire, the Wechsler Brief IQ assessment, and proton magnetic resonance spectroscopic imaging (H-MRSI) to measure subcortical white matter metabolism of choline and related compounds (CHO). Patients with GAD exhibited higher IQ's and lower metabolite concentrations of CHO in the subcortical white matter in comparison to healthy volunteers. In both GAD patients and healthy controls, relatively low CHO predicted both relatively higher IQ and worry scores. Relatively high anxiety in patients with GAD predicted high IQ whereas relatively low anxiety in controls also predicted high IQ. The collective data suggest that both worry and intelligence are characterized by depletion of metabolic substrate in the subcortical white matter and that intelligence may have co-evolved with worry in humans.